Stereoscopic projection lithography based 3D printing with high precision for advanced tissue engineering application - Ma, Jianli; Zhao, Shuo; Li, Yongcheng; Hu, Jingjing; Zhang, Ling; Zhou, Xuan; Yan, Li (Frontiers in Bioengineering and Biotechnology, 2022)
The emergence of tissue engineering technology provides an option for the treatment of early organ and tissue lesions by combination of biomimetic scaffolds and stem cells. Stereoscopic projection lithography is utilized broadly in varied application areas due to its high-precision, resolution, and efficiency features. It can be used to fabricate and manufacture complex scaffolds with hierarchical construct, which are highly suitable for advanced tissue engineering application. In current work, gelatin methacrylate (GelMA) was synthesized and fabricated to bioactive scaffold because of its excellent biocompatibility and biodegradability by using stereoscopic projection lithography based 3D printer (YC-M3D-10). The scaffold displayed multilayered micro structures that supported stem cell growth and promoted cell proliferation. The results demonstrated that the cells proliferated significantly on the printed GelMA scaffold after 6 days. Moreover, GelMA scaffolds can promote cell proliferation and show great prospects in future tissue engineering applications.